Maximally Recoverable LRCs: A field size lower bound and constructions for few heavy parities - Gopi, Sivakanth; Guruswami, Venkatesan; Yekhanin, Sergey (Symposium on Discrete Algorithms (SODA) 2019, 2019)
Talk at Microsoft Research Redmond